Design and evaluation of clickable gelatin-oleic nanoparticles using fattigation-platform for cancer therapy - Meghani, Nilesh M.; Amin, Hardik H.; Park, Chulhun; Park, Jun Bom; Cui, Jing Hao; Cao, Qing Ri; Lee, Beom Jin (International Journal of Pharmaceutics, 2018)
The principles of bioorthogonal click chemistry and metabolic glycoengineering were applied to produce targeted anti-cancer drug delivery via fattigation-platform-based gelatin-oleic nanoparticles. A sialic acid precursor (Ac4ManNAz) was introduced to the cell surface. Gelatin and oleic acid were conjugated by 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride/N-hydroxysuccinimide (EDC/NHS) chemistry with the subsequent covalent attachment of dibenzocyclooctyne (DBCO) in a click reaction on the cell surface. The physicochemical properties, drug release, in vitro cytotoxicity, and cellular uptake of DBCO-conjugated gelatin oleic nanoparticles (GON-DBCO; particle size, ∼240 nm; zeta potential, 6 mV) were evaluated. Doxorubicin (DOX) was used as a model drug and compared with the reference product, Caelyx®. A549 and MCF-7 cell lines were used for the in vitro studies. GON-DBCO showed high DOX loading and encapsulation efficiencies. In A549 cells, the IC50 value for GON-DBCO-DOX (1.29 µg/ml) was six times lower than that of Caelyx® (10.54 µg/ml); in MCF-7 cells, the IC50 values were 1.78 µg/ml and 2.84 µg/ml, respectively. Confocal microscopy confirmed the click reaction between GON-DBCO and Ac4ManNAz on the cell surface. Flow cytometry data revealed that the intracellular uptake of GON-DBCO-DOX was approximately two times greater than that of GON-DOX and Caelyx®. Thus, the newly designed GON-DBCO-DOX provided a safe and efficient drug delivery system to actively target the anticancer agents.
Keywords: A549 Cells; Antibiotics, Antineoplastic; Breast Neoplasms; Cell Survival; Click Chemistry; Doxorubicin; Drug Carriers; Drug Compounding; Drug Liberation; Female; Flow Cytometry; Gelatin; Humans; Lung Neoplasms; MCF-7 Cells; Microscopy, Confocal; Nanoparticles; Nanotechnology; Oleic Acid; Particle Size; Technology, Pharmaceutical; Time Factors; Bio-orthogonal click chemistry; Cancer therapy; Clickable nanoparticles; Doxorubicin; Fattigation-platform; Metabolic glycoengineering